1971
DOI: 10.1530/acta.0.0670535
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of [1,2-3h] Testosterone in Oestrogenized Male Rats

Abstract: A decrease in uptake of tritiated testosterone by the hypothalamus was observed in adult, castrated male rats previously injected with 100 μg oestradiol undecylate on either postnatal days 1 or 5. Moreover, a decrease in pituitary incorporation of labelled testosterone was observed in those animals injected with oestradiol on day 1. Neonatal (5 day) male rats injected with oestradiol 3 hours prior to administering labelled testosterone showed a significant decrease in uptake of label in the pituitary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Using oestradiol benzoate as a probe to identify periods crucial for the development of the male accessory glands, we have confirmed earlier reports (Kincl et al, 1963(Kincl et al, , 1965Harris & Levine, 1965;Simmons, 1971;Lamartiniere et al, 1979) that the neonatal period is particularly critical for growth of the seminal vesicles and ventral prostrate. However, we have extended these morphological observations and shown that the neonatal phase is also important for later functional activity in the adult.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Using oestradiol benzoate as a probe to identify periods crucial for the development of the male accessory glands, we have confirmed earlier reports (Kincl et al, 1963(Kincl et al, , 1965Harris & Levine, 1965;Simmons, 1971;Lamartiniere et al, 1979) that the neonatal period is particularly critical for growth of the seminal vesicles and ventral prostrate. However, we have extended these morphological observations and shown that the neonatal phase is also important for later functional activity in the adult.…”
Section: Discussionsupporting
confidence: 88%
“…A more practicable alternative is to treat the animal with an antagonist to the developmental signal for the duration of the critical time and then discontinue treatment. In selecting such an antagonist, we were guided by previous work where it had been shown that treatment of neonatal rats with oestrogens led to decreased size of the seminal vesicles and ventral prostate in the adult (Kincl et al, 1963(Kincl et al, , 1965Harris, 1964;Harris & Levine, 1965;Simmons, 1971;Lamartiniere et al, 1979).…”
mentioning
confidence: 99%
“…In fact, when compared with androgenized or oestrogenized animals the tumour incidence was higher in intact female rats without oestradiol implant, there were no fibroadenomata, tumours tended to respond better to oestrogens and oestradiol-receptor levels tended to be somewhat higher. The latter finding is of interest since effects of neonatal sex hormones on steroid-receptor concentrations in the uterus, hypothalamus and hypophysis have also been noted by other investigators (Simmons, 1971;Vertes & King, 1971;White, Moore, Elder & Lim, 1981).…”
Section: Discussionsupporting
confidence: 55%
“…But a change occurs in the pattern of diŝ tribution of mitochondria and liposomes approaching that of the female type with values corresponding to those found following neonatal castration (Mäusle 8c Scherrer 1974). As a hypogonadotrophic testo¬ sterone deficit is present in these animals (Kind et al 1964;Schiavi 1968;Frick et al 1969;Kurcz et al 1969;Simmons 1971) together with a persistent feminization of activity patterns of liver enzymes involved in steroid metabo¬ lism (Schriefers et al 1972) there should also be an increased basic activity of the adrenal cortex in comparison with normal males, due to a decrease in the half life of corticosterone. As a hypogonadotrophic testo¬ sterone deficit is present in these animals (Kind et al 1964;Schiavi 1968;Frick et al 1969;Kurcz et al 1969;Simmons 1971) together with a persistent feminization of activity patterns of liver enzymes involved in steroid metabo¬ lism (Schriefers et al 1972) there should also be an increased basic activity of the adrenal cortex in comparison with normal males, due to a decrease in the half life of corticosterone.…”
Section: Discussionmentioning
confidence: 99%